Experimental investigation of H-DLC coated exhaust valve characteristics of a diesel engine. (2020) - Sivakumar, E.R.; Senthilkumar, P.; Sreenivasan, M.; Krishna, Ram
Abstract: In the present research work, the exhaust valve was coated with the hydrogenated diamond like carbon (H-DLC) material with different thicknesses such as 2, 3, 4, 5, and 6 µm over the whole surface using magnetron sputtering technique. The main emphasis was on optimizing the best coating thickness and studying the effect of diesel engine performance characteristics at varying load conditions. The study showed that brake thermal efficiency (BTE) and NOx emissions were increased and the specific fuel consumption (BSFC), CO and HC emissions were decreased for thermal coated exhaust valve compared with the base engine. The peak cylinder pressure for 4 µm thickness coating increased upto 8.30% in the TBC engine, specifically at high power output; however, the exhaust gas temperatures were generally lower, signifying noble gas expansion in the power stroke that in turn increased the peak cylinder pressure and enhanced the BTE which increased by 1.6%. From the result it could be inferred that the engine with DLC coated valve enhanced the engine performance up to an optimum coating thickness beyond which the performance of the engine declined. The coated and uncoated surfaces were characterized by EDS and their microstructures were analyzed by SEM.